2010
DOI: 10.1590/s0100-736x2010000900015
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular pressure and tear secretion in Saanen goats with different ages

Abstract: This study aimed to compare the normal intraocular pressure (IOP) and tear secretion, by means of applanation tonometry and the Schirmer tear test-1 (STT-1), in goats of the Saanen breed with different ages, and at different time points. Thirty six goats, free of ocular abnormalities, were grouped into three different age categories (n=12), animals with 45, 180 and 549 days of age. STT-1 and IOP measurements were carried out always at 9:00am and 7:00pm, during three consecutive days. Results were evaluated sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…An additional aim was to check for differences in the values of intraocular pressure between genders and between different age groups of chinchillas. Age-related differences in IOP have been reported (GELATT & MACKAY, 1998;NOMURA et al, 1999;RIBEIRO et al, 2010). In the present research, no significant differences were found in IOP between genders as reported in literature (GELATT & MACKAY, 1998;MERCADO et al, 2010;RUSANEN et al, 2010;PEREIRA et al, 2011).…”
Section: Discussionsupporting
confidence: 55%
“…An additional aim was to check for differences in the values of intraocular pressure between genders and between different age groups of chinchillas. Age-related differences in IOP have been reported (GELATT & MACKAY, 1998;NOMURA et al, 1999;RIBEIRO et al, 2010). In the present research, no significant differences were found in IOP between genders as reported in literature (GELATT & MACKAY, 1998;MERCADO et al, 2010;RUSANEN et al, 2010;PEREIRA et al, 2011).…”
Section: Discussionsupporting
confidence: 55%
“…There are quite a few studies using applanation tonometry in animals (Priehs et al, 1990;Miller et al, 1990;Miller et al, 1991;Dziezyc et al, 1992;Passaglia et al, 2004;Candia et al, 2010;Gerometta et al, 2010;Ribeiro et al, 2010;Rusanen et al, 2010), but we found no reports on the assessment of the mean IOP in healthy sheep using the applanation tonometer Tonopen XL e . The purpose of this study was to determine the mean IOP in healthy adult sheep using applanation tonometry with Tonopen XL e .…”
Section: Introductionmentioning
confidence: 61%
“…Ocular factors that contribute to IOP across species result from anatomical and physiological differences in ciliary body, aqueous humor drainage, corneal curvature and rigidity , Ribeiro et al 2010, extraocular muscular tone, eyelid closure and muscular retraction of the eyeball (Ribeiro et al 2010). Other factors that can affect IOP include age, race, weight, season and circadian cycle (Ofri 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Reports in the literature related interference of the circadian cycle on IOP in Saanen goats (Ribeiro et al 2010) and cats (Sole et al 2007). An increase in IOP is related to the animal's active period and researchers observed an IOP peak during the night in cats (Sole et al 2007).…”
Section: Discussionmentioning
confidence: 99%